2022
DOI: 10.1097/qad.0000000000003161
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of SARS-CoV-2 vaccines in people with HIV

Abstract: Objective:To evaluate the safety and the serological response after two doses of mRNA-based SARS-CoV-2 vaccination in people with HIV (PWH).Methods:Participants were evaluated 4 weeks after the second dose of mRNA-1273 or BNT162b2 vaccine. Tolerability was evaluated with a specific adverse event questionnaire. Patient's sera were analysed using LIAISON SARS-CoV-2 TrimericS IgG (DiaSorin).Results:One-hundred PWH were included, 75% of them men, with a mean age of 44 ± 11 years old, all receiving antiretroviral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Tables S1 and S2 present the serological antibody titers after a first and second dose of COVID-19 vaccines, respectively. In addition, one study that met the inclusion criteria for meta-analysis was excluded because seroconversion rates among healthy controls could not be obtained in time from the corresponding authors ( González de Aledo et al, 2022 ).
Figure 1 Flowchart of study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…Tables S1 and S2 present the serological antibody titers after a first and second dose of COVID-19 vaccines, respectively. In addition, one study that met the inclusion criteria for meta-analysis was excluded because seroconversion rates among healthy controls could not be obtained in time from the corresponding authors ( González de Aledo et al, 2022 ).
Figure 1 Flowchart of study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…Another 14 studies were further removed for failing to report seroconversion (n = 6), cross-sectional studies (n = 5), reviews (n = 2), and failing to provide HIV-infected patients (n = 1) (Table S3). Finally, 50 studies with a total of 7160 patients living with HIV were included for our meta-analysis 11,12, , 30 studies were included for qualitative analysis of serological antibody titers (Table S4 to 6); 46 studies 11,12,[17][18][19][20][21][22][23][24][25][27][28][29][30][31][32][34][35][36][37][38][39][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][58][59][60][61][62][63][64] were included for quantitative analysis of pooled seroconversion rates; 34 studies 11,…”
Section: Results Study Selection Characteristics and Quality Assessmentmentioning
confidence: 99%
“…These studies showed a decrease both in humoral and cellular immunity at 6 months, despite no significant difference being found compared to a cohort of HIV-uninfected people vaccinated with the same vaccine. To date, only few observational studies were carried out about the effectiveness of mRNA vaccines in this group of patients, and all showed a good humoral and cellular immune response after the primary vaccination cycle in patients on HAART and with CD4+ cell counts >200 cell/mm 3 [ 41 , 42 , 43 ]. However, the response is significantly lower in PLWH with CD4+ cell counts <200/mm 3 compared to those with a count >500 cell/mm 3 and HIV-uninfected controls.…”
Section: Discussionmentioning
confidence: 99%